2019
DOI: 10.1016/j.pedneo.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting body composition in preterm infants: Assessment techniques and nutritional interventions

Abstract: Limited research has been conducted that elucidates the growth and body composition of preterm infants. It is known that these infants do not necessarily achieve extra-utero growth rates and body composition similar to those of their term counterparts. Preterm infants, who have difficulty in achieving these growth rates, could suffer from growth failure. These infants display an increased intra-abdominal adiposity and abnormal body composition when they achieve catch-up growth. These factors affect the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Thus, results evidenced the disadvantage of EUGR after preterm birth to develop a higher inflammatory status. Changes in the adipose tissue and body composition during the early postnatal period, in response to an unfavourable extrauterine environment, could be involved (8). TNF-α, involved markedly in systemic inflammation (50), is chiefly produced by the macrophages of the adipose tissue, and its levels have been positively related to MCP-1 and HGF values (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, results evidenced the disadvantage of EUGR after preterm birth to develop a higher inflammatory status. Changes in the adipose tissue and body composition during the early postnatal period, in response to an unfavourable extrauterine environment, could be involved (8). TNF-α, involved markedly in systemic inflammation (50), is chiefly produced by the macrophages of the adipose tissue, and its levels have been positively related to MCP-1 and HGF values (19).…”
Section: Discussionmentioning
confidence: 99%
“…The literature over the last several decades has highlighted how prematurity not only affects physical growth (1) and neurodevelopment (2) during infancy and childhood, but also is a possible risk factor for the development of cardiometabolic complications (3) such as hypertension (4), metabolic syndrome (5), type 1 and type 2 diabetes (6), and cardiovascular disease (CVD) (4,5). The mechanisms involved in this programming have been studied, and postnatal growth may be impactful on this metabolic dysregulation (7,8). Extrauterine growth restriction (EUGR) represents the failure of very preterm infants to reach their potential growth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were not excluded based on methods used for measuring growth parameters or body composition, as some of these methods are suggested to be more accurate but also more expensive or less applicable to newborn infants [14]. The use of these methodologies is further explained in the studies.…”
Section: Methods To Measure Growth Parameters and Body Compositionmentioning
confidence: 99%
“…Although the effects of (early) infancy weight gain on later body composition and health outcomes are not clear, associations with an aberrant fat distribution, cardiovascular diseases, and an obesity-associated exacerbation of renal risk have been suggested [8][9][10][11][12]. It is suggested that an altered body composition that persists into adulthood could be a risk factor for developing metabolic and cardiovascular diseases, although it could not always be identified as a causal factor [3,5,9,13,14]. However, the ideal growth pattern for ELBW infants is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Undernutrition in preterm infants is associated with serious consequences such as increased mortality and long-term neurodevelopmental, metabolic, and growth disorders. 3 Undernutrition largely affects the brain, resulting in poor brain growth and neurodevelopmental delay. 4 Regardless of the degree of prematurity, early postnatal growth (ie, during hospitalization) has been associated with neurological and cognitive outcomes in infancy and preschool-age.…”
Section: Introductionmentioning
confidence: 99%